The Potential of Harnessing IL-2-Mediated Immunosuppression to Prevent Pathogenic B Cell Responses - Papillion, Amber; Ballesteros-Tato, André (Frontiers in Immunology, 2021)
Immunosuppressive drugs can partially control Antibody (Ab)-dependent pathology. However, these therapeutic regimens must be maintained for the patient's lifetime, which is often associated with severe side effects. As research advances, our understanding of the cellular and molecular mechanisms underlying the development and maintenance of auto-reactive B cell responses has significantly advanced. As a result, novel immunotherapies aimed to restore immune tolerance and prevent disease progression in autoimmune patients are underway. In this regard, encouraging results from clinical and preclinical studies demonstrate that subcutaneous administration of low-doses of recombinant Interleukin-2 (r-IL2) has potent immunosuppressive effects in patients with autoimmune pathologies. Although the exact mechanism by which IL-2 induces immunosuppression remains unclear, the clinical benefits of the current IL-2-based immunotherapies are attributed to its effect on bolstering T regulatory (Treg) cells, which are known to suppress overactive immune responses. In addition to Tregs, however, rIL-2 also directly prevent the T follicular helper cells (Tfh), T helper 17 cells (Th17), and Double Negative (DN) T cell responses, which play critical roles in the development of autoimmune disorders and have the ability to help pathogenic B cells. Here we discuss the broader effects of rIL-2 immunotherapy and the potential of combining rIL-2 with other cytokine-based therapies to more efficiently target Tfh cells, Th17, and DN T cells and subsequently inhibit auto-antibody (ab) production in autoimmune patients.